2014
DOI: 10.1186/s12917-014-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of the HRM method for identifying possible mutations in the ymoA gene region and evaluating their influence on the enterotoxic properties of Y. enterocoliticastrains

Abstract: BackgroundThe yst gene that encodes the production of Yst enterotoxins is one of the most important and reliable virulence markers. Its ability to produce Yst has been demonstrated in pathogenic strains isolated from clinical cases of yersiniosis with diarrhea. However, not all yst positive strains produce enterotoxins. According to some authors, Yst production can be restored in a silent strain by ymoA mutation. In this study, the HRM method was applied to identify ymoA single nucleotide polymorphism with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, the results of our previous study 23 show that two point mutations in the nucleotide sequence of the ymoA gene, which were detected with the use of the High-Resolution Melting (HRM) method, did not in uence on enterotoxic properties of the examined strains. Mikulskis et al 9 in 1994 presented the mechanism modifying the expression of yst to a silent state.…”
Section: Introductionmentioning
confidence: 89%
“…However, the results of our previous study 23 show that two point mutations in the nucleotide sequence of the ymoA gene, which were detected with the use of the High-Resolution Melting (HRM) method, did not in uence on enterotoxic properties of the examined strains. Mikulskis et al 9 in 1994 presented the mechanism modifying the expression of yst to a silent state.…”
Section: Introductionmentioning
confidence: 89%
“…According to best knowledge of the authos', this is one of the few studies where the HRM method was deployed to characterize Y. enterocolitica strains. Bancerz-Kisiel et al [16] used HRM to detect possible mutations in the ymoA (Yersinia Phylogenetic analysis of G1 nucleotide sequences ystB gene Y. enterocolitica strains isolated from wild animals revealed 100% similarity with the Y. enterocolitica D88145.1 sequence. Analysis of G2 nucleotide sequences ystB gene revealed one point mutation in the examined region: transition T111A.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution melting (HRM) analysis is an emerging method for the detection of single nucleotide polymorphisms (SNPs) and for SNPs-based genotyping [16,17]. In this method, the reduction in fluorescence is carefully monitored when a PCR product stained with a double-strand-specific fluorescent dye is heated through its melting temperature (T m ) [18].…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Mikulskis et al [ 83 ] also postulated the inherence of a mechanism switching the yst expression to a silent state, and other authors showed that yst gene presence is not always correlated with YstI production [ 85 , 95 ]. In the study of Bancerz-Kisiel et al [ 96 ], no mutations were found in the coding region of the examined ymoA gene fragments. Two point mutations in the non-coding region have been identified in some of the tested Y. enterocolitica strains, regardless of their enterotoxic properties [ 96 ].…”
Section: Pathogenesis Of Y Enterocolitica Infementioning
confidence: 97%
“…In the study of Bancerz-Kisiel et al [ 96 ], no mutations were found in the coding region of the examined ymoA gene fragments. Two point mutations in the non-coding region have been identified in some of the tested Y. enterocolitica strains, regardless of their enterotoxic properties [ 96 ]. Hence, the suggestion that ymoA gene mutations influence ystA gene silencing was not confirmed.…”
Section: Pathogenesis Of Y Enterocolitica Infementioning
confidence: 97%